Fishes from Chira River basin, Piura, Peru - Meza-Vargas, Vanessa (2022)
Chira River is located on the north coast of Peru. The lack of knowledge of the ichthyofauna from coastal drainages from Peru is noteworthy. The aim of this study is to characterize the ichthyofauna along the Chira River basin in terms of diversity and altitudinal range distribution. The material examined belongs to the Ichthyological collection of the Natural History Museum (MUSM). The diversity of fishes is composed of 27 species belonging to 19 families and ten orders. Siluriformes and Characiformes were the most diverse, consisting of 22% (six species) for each one. Five species are new records for the Chira River (three natives and two non-natives). Six marine species and seven exotic species were recorded as well. The altitudinal distribution patterns for all species were registered. This study increases the known diversity of freshwater fishes from Pacific Drainage Rivers in Peru, and it could be used for management and conservation plans.